P231 Cardiac metastasis mimicking a myocardial infarction. (17th January 2020) - Chiampan, A; Lanzoni, L; Lanzoni, L; Adamo, E; Adamo, E; Dugo, C; Dugo, C; Bonapace, S; Bonapace, S; Castagna, F; Castagna, F; Barbieri, E; et al.
Abstract: We present the case of a 79 years old male patient affected by a lung squamous cell carcinoma (T4 N0 M1a) diagnosed in december 2018 with a 5x5 cm mass in the inferior lobe of the left lung close to the pericardium and a second 5 cm mass in the apical lobe of the right lung. TT echocardiography at that time was normal. Treatment with gemcitabine was scheduled with slight progression of the disease at the CT scan control in april 2019 when initial invasion of the left inferior pulmonary vein was detected. An ECG performed during routine control revealed the presence of q waves and ST segment elevation in the inferior leads. The patient was asymptomatic about the heart but the blood tests revealed a slight increase of HS Troponin I. We decided to repeat the TT echo, which showed the presence of a rounded mobile mass of about 3x2.5 cm in the left atrium close to the upper left pulmonary vein and another formation of about 5x2 cm infiltrating the inferior wall of the left ventricle that appeared akynetic. Both metastatic and thrombotic origins were debated and anticoagulant therapy with LMWH was started. We chose to perform a TE echocardiography, which confirmed the presence of the rounded mass in the left atrium, enlarged as compared to the TT evaluation. At the 3D reconstruction, it appeared to come from the left inferior pulmonary vein, completely occluding it, and expanding to the left superior vein, narrowing but not closing its orifice. The mass was well delimitated, disomogenous and vacuolated, thus confirming its likely neoplastic origin. From the trans-gastric view, we confirmed the large infiltration of the inferior wall of the left ventricle. General conditions of the patients quickly deteriorated and he experienced an ischemic stroke. At the TT echo re-evaluation the mass in the left atrium was greatly reduced as compared to the previous control. Cardiac metastases are a rare and frequently clinically silent occurrence; However, in a minority of cases they may present with ECG alterations such as ST-T segment modifications. In neoplastic patients an ischaemic ECG pattern not following its typical progression, without typical symptoms of ischaemia should rise the suspicion of a cardiac metastasis. In our case the abnormalities could be caused by a loss of viable myocardium secondary to the infiltrating mass or by a compression of the right coronary artery. In this context the echocardiography, both TT and especially TE, is a valuable tool that allow to recognize the real cause of these abnormalities and provides useful informations that enable to distinguish neoplastic mass from a thrombus. The ischaemic stroke was probably due to an embolization of the mass from the left atrium, as confirmed by its important reduction at the last echo control.